Eine ethik für den gesamten planten: gedanken über den eigenwert der natur - Rolston, Holmes, 1932-2025, author; Gesellschaft für Ökologisch-Nachhaltige Entwicklung, publisher (Colorado State University. Libraries, 2006)
Every living organism conserves its life and in that sense conservation is innate in biology. Non-conservation is death. Organisms have goods of their own, conserved and elaborated in species lines, resulting in the biodiversity on Earth. Concern for preserving nature, such as wilderness recognizes instrumental, intrinsic, and systemic values in nature. In the modern world, much of such wild nature has ended by transformation into human dominated landscapes. But nature ought also to be on end in itself.
An ethic for the whole planet: thoughts about the intrinsic value of nature
Chapters 6 and 7 of Conserving Natural Value (New York: Columbia University Press, 1994).
Keywords: conservation biology; intrinsic value; natural value; wilderness; nature as end in itself